Correlation Between Knowledge And Motivation of Primigravid Mothers With Interest In Initiating Early Breastfeeding At Muhammadiyah Gresik Hospital - Zahroh, Umi Rifa’ati; Zuhroh, Diah Fauzia; Fitrianur, Widya Lita (Kontribusia : Research Dissemination for Community Development, 2024)
Implementation of Early Breastfeeding Initiation (IMD) is the beginning of success in exclusive breastfeeding. Ignorance and lack of information about early breastfeeding make primigravida mothers less motivated, so mothers are not interested in doing IMD. The purpose of this study was to determine correlation between the knowledge and motivation of primigravida mothers with their interest in IMD at Muhammadiyah Gresik hospital. The design of this research is correlational analytic with cross sectional approach. The sampling technique used purposive sampling with a sample of 108 primigravida mothers. The study used IMD knowledge, motivation, and interest questionnaires, and then used the Spearman rank test. The result showed that most of the primigravida mothers who checked at the obstetrical polyclinic at Muhammadiyah Gresik Hospital had sufficient knowledge of 61 (56.5%) mothers, moderate motivation of 64 (59.2%) mothers, and moderate interest of 68 (63%) mothers. The results showed that the value of knowledge was p = 0.000 < α 0.05 and the value of motivation was p = 0.000 < α 0.05. From this study can be conclused that there is a correlation between the knowledge and motivation of primigravida mothers with interest in Early Breastfeeding Initiation at Muhammadiyah Gresik Hospital.